The Effect Of Drill Method Training Of Target Games On Extracurricular Futsal Shooting At State Vocational High School 1 South Bengkulu - Saputra, Dio Cahyo; Asnawati, Asnawati; Martiani, Martiani (Journal of Physical Education and Sports, 2025)
The purpose of this study was to determine the effect of the target game drill method on the shooting ability of futsal players of SMK Negeri 1 Bengkulu Selatan. This type of research is experimental research. The sample in this study were all extracurricular Futsal players of SMK Negeri 1 Bengkulu Selatan totalling 16 people. . The results of testing the hypothesis that the overall group obtained a mean initial test value of 18.31 standard deviation 5.67, a minimum value of 10, and a maximum value of 29, and a final test mean of 26.50, a standard deviation of 6.78, a minimum value of 15, and a maximum value of 35. Based on the measurement of the initial test and the final test using the t-test statistical approach of the overall training method group t count = 4.222 and t table (α = 0.05) = 1.753 which means t count> t table, so it can be concluded that there is a significant influence between the practice of the target game driil method on the shooting skills of futsal players of SMK Negeri 1 Bengkulu Selatan. With the formalisation as stated in the previous theoretical study, the practice of the target game practice method is effective in improving futsal shooting skills.